Dynamics of Hemoglobin A1c, Body Mass Index, and Rates of Severe Hypoglycemia in 4434 Adults with Type 1 or Type 2 Diabetes After Initiation of Continuous Glucose Monitoring - Lanzinger, Stefanie; Best, Frank; Bergmann, Tanja; Laimer, Markus; Lipovsky, Boris; Danne, Thomas; Zimny, Stefan; Bramlage, Peter; Meyhoefer, Svenja; Holl, Reinhard W. (Diabetes Technology & Therapeutics, 2022)
Background: Continuous glucose monitoring (CGM) might have beneficial effects on glycemic control and body mass index (BMI) in adults with type 1 (T1D) or type 2 diabetes (T2D).Methods: The diabetes prospective follow-up registry was used to identify individuals with T1D or T2D >= 18 years starting CGM management in 2015 or later and follow-up information available. Hemoglobin A1c (HbA1c), BMI, and event rates of severe hypoglycemia in the year before CGM start were compared with two follow-up periods: (1) CGM use for 3-6 months and (2) CGM use for >6 months. Repeated measurements linear and negative binomial regressions were used (adjustment for sex, age at diabetes onset, and baseline parameters) and stratified by diabetes type.Results: Mean follow-up time was 1.8 years in T1D (n = 2994) and 1.9 years in T2D (n = 1440). In T1D, adjusted mean HbA1c decreased significantly from 7.65% (95% confidence interval: 7.62-7.68) at baseline to 7.54% (7.51-7.57) during follow-up. BMI increased slightly (baseline: 25.4 kg/m(2) [25.3-25.5], follow-up >6 months: 25.8 kg/m(2) [25.7-25.9]), whereas event rates of severe hypoglycemia were significantly lower after >6 months with CGM (9.0 events/100 patient-years [PY; 8.0-10.1]) compared with baseline (11.3 events/100 PY [10.4-12.2]) in adults with T1D. In T2D, HbA1c decreased from 7.21% (7.17%-7.25%) to 7.00% (6.95%-7.04%) and BMI did not change after CGM initiation.Conclusion: Our results provide real-world evidence on CGM management in adult individuals with T1D or T2D. We suggest strengthening patients' and physicians' readiness toward diabetes technology in T2D and more openness of health insurance to cover cost based on proven benefits.
CRIS-Team WoS Importer:2022-07-22